1994
DOI: 10.1073/pnas.91.8.3067
|View full text |Cite
|
Sign up to set email alerts
|

The retinoid X receptor ligand, 9-cis-retinoic acid, is a potential regulator of early Xenopus development.

Abstract: Endogenous retinoids are potential regulators of vertebrate embryogenesis that have been implicated in early anterior-posterior patterning and limb-bud development. We have characterized the temporal and spatial distribution of 9-cis-retinoic acid in the Xenopus embryo and compared it to two other retinoids, afl-tmns-retinoic acid and alI-frns-retinoyl-3glucuronide. 9-cis-Retinoic acid is first detected after the midblastula transition and by the end of gastruation is localz primarily within the anterior and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
2
1

Year Published

1995
1995
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 37 publications
1
52
2
1
Order By: Relevance
“…In addition, there are other differences between lower vertebrates and higher vertebrates. In Xenopus (Durston et al, 1989;Kraft et al, 1994) and zebrafish (Costarides et al, unpublished results) retinal is the major retinoid present in embryos, with t-retinol playing a minor role, whereas in chicks and mouse, retinal is undetectable (Thaller and Eichele, 1987; and these results) and retinol is the major retinoid. Thus in several respects retinoid metabolism seems to be quite distinct in different classes of vertebrate.…”
Section: Discussion Endogenous Retinoids In the Mouse Embryomentioning
confidence: 90%
See 3 more Smart Citations
“…In addition, there are other differences between lower vertebrates and higher vertebrates. In Xenopus (Durston et al, 1989;Kraft et al, 1994) and zebrafish (Costarides et al, unpublished results) retinal is the major retinoid present in embryos, with t-retinol playing a minor role, whereas in chicks and mouse, retinal is undetectable (Thaller and Eichele, 1987; and these results) and retinol is the major retinoid. Thus in several respects retinoid metabolism seems to be quite distinct in different classes of vertebrate.…”
Section: Discussion Endogenous Retinoids In the Mouse Embryomentioning
confidence: 90%
“…combining the methods of Thaller and Eichele (1987) and Kraft et al (1994), separation was achieved. Fractionation of day 12 embryo extracts showed that 9-cis-RA was undetectable a t this stage of development (data not shown).…”
Section: Endogenous Retinoids In Whole Mouse Embryosmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is known that exogenous 9 4 s RA can cause duplications in the chick wing (Thaller et al, 1993). It seems also to be involved in the dysmorphogenesis of embryonic structures in the rat (Creech Kraft and Juchau, 1993) and in Xenopus (Dawid et al, 1993;Creech Kraft et al, 1994). Most recently, Creech Kraft et al, (1994) examined the spatial and temporal distributions of endogenous 9 4 s RA in Xenopus embryos.…”
Section: Introductionmentioning
confidence: 99%